Analisis Kemampuan Bahasa Mandarin terhadap Kinerja Mahasiswa Magang Internasional di Taiwan - Agus Suhara; Renny Aprilliyani (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This article aims to analyze Mandarin language proficiency and its influence on the performance of Indonesian students participating in international internship programs in Taiwan. The research problem focuses on students’ Mandarin language ability and its impact on work communication, task completion, and adaptation to an international work environment. This study employed a qualitative descriptive approach. Data were collected through in-depth interviews with 10 Indonesian students who were currently participating in or had completed internship programs in various companies in Taiwan, supported by observation and documentation. The data were analysed using data reduction, data display, and conclusion drawing techniques. The findings show that listening and speaking skills are the most dominant Mandarin competencies used in workplace communication. Students with higher Mandarin proficiency tend to understand job instructions more quickly, adapt more easily to the work environment, and demonstrate greater confidence in communicating with supervisors and colleagues. In contrast, students with limited language ability experience difficulties at the initial stage of the internship, particularly in understanding fast speech and technical job terminology, which slows down their adaptation process. This study concludes that Mandarin language proficiency has a significant influence on Indonesian students’ performance in international internship programs in Taiwan, especially in improving communication effectiveness and workplace adaptation.